PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ASIH LESTARI CAKE KABUPATEN BANDUNG - Riska Rahayu; Wawat Setiawati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine how product price and quality influence purchasing decisions at Toko Asih Lestari Cake in Bandung Regency. This study uses a quantitative method with a descriptive and verificative approach. The study involved 96 participants, determined using Lemeshow's formula. The data analysis techniques used include validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and the coefficient of determination.The results of the multiple linear regression analysis show the equation Y = 2,314 + 0,352X₁ + 0,487X₂. Partially, the price variable (X₁) has a significant effect on the purchase decision, with a calculated t-value of 3.215, which is greater than the table t-value of 1.985, and a significance value of 0.002, which is less than 0.05. The quality of the product variable (X₂) has a significant effect, as shown by a calculated t-value of 4.876, which is greater than 1.985, and a significance level of 0.000, which is less than 0.05. At the same time, both the price and quality of the product have a significant effect on the purchasing decision, with an F value of 45.632, which is greater than the F table value of 3.09, and a significance level of 0.000, which is less than 0.05. The coefficient of determination (R²) value of 0.495 shows that 49.5% of the purchase decisions are influenced by product price and quality, while the remaining part is affected by other factors not included in this study.